A Modified Bridgeless Converter for SRM Drive with Reduced Ripple Current - Maheswari C krishnakumar; Rani Thottungal; Divya A.C (Institute of Advanced Engineering and Science, 2015)
Single Phase Switched Reluctance Motor is more popular in many industrial purposes for high speed applications because of its robust and rugged construction. For low cost and variable speed drive applications SRM are widely used.Due to doubly salient structure of motor, the torque pulsations are high when compared to other sinusoidal machines. The major drawback in using SRM drive is torque pulsations and increased number of switching components. In order to overcome these drawbacks, a bridgeless Single Ended Primary Inductor Converter (SEPIC) is proposed. The major advantages of this converter are continuous output current,smaller voltage ripple and reduced semiconductor current stress when compared to the conventional SEPIC converter. The ripple free input current is obtained by using additional winding of input inductor and auxiliary capacitors. To achieve high efficiency, active power factor correction circuits (PFC) are employed to precise the power factor. Further, the unity power factor can be obtained by making the input current during switching period proportional to the input voltage is proposed. The proposed system consists of reduced components and it is also capable of reducing the conduction losses. The working principles and the waveforms of proposed converter are analyzed. To analyze the circuit operation, theoretical analysis and simulation results are provided. Finally, the comparison between the waveforms of conventional SEPIC and proposed system is presented by using MATLAB/Simulink tools.